A Study on Defining Communicative Characteristics of Public Libraries - noh, younghee; woojung, kwak; Kim, Yoon Jeong (International Journal of Knowledge Content Development & Technology, 2024)
This study intended to discover the communicative characteristics of libraries, such as locality, communality, interactivity, and organic vitality, and measure as to whether the components constituting them were appropriate, and based on the research results, it was intended to establish the role of public libraries based on communicative characteristics. As a result of the study, it finally turned out that the libraries had the four communicative characteristics of 'locality', 'communality', 'interactivity', and 'organic vitality'. The four communicative characteristics may be classified into 16 factors and 63 detailed factors accordingly. Examining the characteristics of library communication, first, locality means that local residents create and maintain the identity of a social, historical, and cultural locality while sharing the space of a library. In the library, the users can receive local life information or create a cultural identity of the locality through communication between the users. Second, communality is a fundamental factor in forming a community of local residents and represents the characteristics of a group formed based on place and geographical characteristics, culture and belief system, and interests. Third, interactivity refers to a kind of behavior in which users interact with other users, information providers, and books and information in the library to give and receive influence. The actions in which two or more objects share knowledge, thoughts, emotions, and opinions may be seen as being accomplished through interaction. Lastly, organic vitality means seeking the continuous maintenance and development of the community, and creating a lasting characteristic even in the changing environment of the library.